Structural analysis of $$\hbox{Sn}$$ on $${\hbox{Au}(111)}$$ at low coverages: Towards the $${\hbox {Au}_{2}\hbox {Sn}}$$ surface alloy with alternating fcc and hcp domains - Julian A. Hochhaus; Stefanie Hilgers; Marie Schmitz; Lukas Kesper; Ulf Berges; Carsten Westphal (Scientific Reports, 2025)
Abstract We report on the structural and chemical evolution of submonolayer $$\hbox{Sn}$$ on $${\hbox{Au}(111)}$$ up to the formation of the striped $${\hbox {Au}_{2}\hbox {Sn}}$$ surface alloy. Using Low-Energy Electron Diffraction (LEED) and Scanning Tunneling Microscopy (STM), we identify a previously unobserved hexagonal $$(2× 2)$$ -reconstruction at a $$\hbox{Sn}$$ film thickness of $$≈ 0.28$$ monolayers (ML). X-ray Photoelectron Spectroscopy (XPS) analysis reveals that the $$(2× 2)$$ -structure is not chemically bonded to the $${\hbox{Au}(111)}$$ substrate. With increasing $$\hbox{Sn}$$ coverage, the $$(2× 2)$$ -reconstruction performs a structural transition into a mixed phase before forming a local $$(\sqrt{3} × \sqrt{3})\text {R}{30}^{° }$$ -reconstruction at a $$\hbox{Sn}$$ film thickness of $$0.33\,ML$$ . This reconstruction is superimposed by a larger periodicity resembling the herringbone reconstruction of clean $${\hbox{Au}(111)}$$ . Our XPS analysis identifies this phase as an $${\hbox {Au}_{2}\hbox {Sn}}$$ -alloy. By combining high-resolution x-ray photoelectron diffraction (XPD) measurements of $$\hbox{Au}\,\hbox{4f}$$ and $$\hbox{Sn}\,\hbox{4d}$$ 4d core levels with simulations based on a genetic algorithm, we propose a structural model for the $${\hbox {Au}_{2}\hbox {Sn}}$$ -supercell, revealing an unusually large unit cell with $$\text {Rec}(26× \sqrt{3})$$ -periodicity. This study advances the understanding of the structural evolution of $$\hbox{Sn}$$ surface reconstructions on $${\hbox{Au}(111)}$$ up to the formation of the $${\hbox {Au}_{2}\hbox {Sn}}$$ surface alloy. Furthermore, it provides insights into the structural arrangements emerging at higher submonolayer $$\hbox{Sn}$$ coverages on $${\hbox{Au}(111)}$$ , offering potential pathways towards realizing freestanding stanene.